Analisis Regresi dan Korelasi Antara Kualitas Produk terhadap Keputusan Pembelian Produk Smartphone Oppo di Kota Pariaman - Dedi Mardianto; Deby Handayani; Zaki (SAFE-Network, 2023)
This study is entitled regression analysis and correlation between product quality and purchasing decisions for Oppo smartphone products in Kota Pariaman. Statistical science can be used in estimating consumer purchasing decisions involving product quality. The number of respondents amounted to 16 data taken by the proposive sampling method. The method used is Simple Linear Regression. The result of the equation is Y ̂=184.41-0.6X. The degree of relationship or Pearson correlation between variables X and Y is 77.7% which is categorized as having a high relationship. While the results of the F test obtained F count of 47.85 and F table of 4.6, because the results of F count were greater than F tables, which meant that the product quality variable had an effect on the purchasing decision variable.